(AlN)xMo1 − x (x = 0.5) composite fabricated by spark plasma sintering (SPS). (January 2016) - Zhang, Jinyong; Hu, Wen; Zhang, Fan; Fu, Zhengyi
Abstract: Spark Plasma Sintering (SPS) was used to fabricate (AlN)x Mo1 − x (x = 0.5) composites in this work. The chemical stability, densification mechanism and microstructure evolution of the system were focally investigated by SPS, as well as the effects of their microstructure on their properties. Results show that rapid densifications were attained by SPS due to the Mo plastic deformation mechanism, greatly inhibiting the Mo grain growth and resulting in remarkable improvements of the mechanical properties, such as a flexural strength of 811.2 MPa, a Rockwell hardness of 88.5 and a thermal conductivity of 92.9 W/(m*K). When the sintering temperature was increased to 1900 °C, an unexpected chemical reaction occurred as well as the recordable AlN grain growth that greatly degraded the flexural strength of the composites. Highlights: We reported the fabrication, properties and microstructure of (AlN)x Mo1-x (x = 0.5) composite by SPS. Mo-plastic deformation dominated the densification of this composite, resulting in a rapid densification, which greatly inhibited the Mo grain growth and the possible chemical reaction of this system. The rapid densification remarkably improved the properties, such as the flexural strength of 811.2 MPa, the Rockwell hardness of 88.5 and the thermal conductivity of 92.9 W/(m*K) of sample sintered at 1800°C.